Exploring the Impact of Human Immunodeficiency Virus on Hepatitis B Virus Diagnosis, Prevention and Control in Co-infected Adult South African Patients on Highly Active Antiretroviral Therapy - Lukhwareni, Azwidowi (University of Limpopo (Medunsa), 2008)
Background and Objectives: South Africa is one of the countries highly affected by human immunodeficiency virus (HIV) and hepatitis B virus (HBV) infections. Some drugs (e.g. lamivudine) used as part of combination antiretroviral regimens for HIV treatment have dual activity against HBV and HIV. Despite high infection rate with both viruses, routine screening for HBV before initiation of treatment for HIV is not yet a standard practice. This study undertook to investigate: (1) the burden of HBV co-infection in HIV-positive patients enrolling for highly active antiretroviral therapy (HAART) at Dr George Mukhari hospital, (2) the impact of anti-HBV containing HAART regimens on HBV during the management of HBV/HIV co-infected patients, (3) the co-evolution of HBV and HIV drug-resistant strains, and (4) the correlation of HBV genotypes with response to anti-HBV containing HAART regimens. Study Population and Methods: To investigate the burden of HBV/HIV co-infections, a cohort of 192 HIV patients who were candidates for ARV treatment at Dr George Mukhari hospital were studied by screening for HBV serological markers (HBsAg, anti-HBs and anti- HBc) (Elecsys 2010, Roche Diagnostics) and HBV DNA with an in-house nested PCR assay targeting HBV polymerase gene. Quantitation of HBV DNA positive samples was performed with Roche Cobas Taqman HBV test 48 assay. To investigate the impact of lamivudine-containing HAART regimens on HBV during the management of HBV/HIV co-infected patients, as well as the coevolution of HBV and HIV drug-resistant strains, a total of 78 patients were studied. HBV virological response against lamivudine containing-HAART regimens [1a (lamivudine, stavudine and efaverenz); 1b (lamivudine, stavudine and neviripine)] was measured (Cobas Taqman HBV test 48, Roche diagnostics). HBV direct sequencing targeting HBV polymerase gene was performed on all baseline samples (n=78) and additional samples collected at various time points (n = 45). Direct sequencing was also performed on 30 HIV baseline samples targeting the HIV reverse transcriptase and protease genes (Spectru-Medix SCE 2410 Genetic Analysis System and ABI PRISM® 3100 Genetic Analyzer version 3.7). To explore the genetic diversity of HBV and HIV strains circulating in Pretoria and surrounding areas, as well as the correlation of HBV genotypes with response to lamivudine-containing-HAART regimens in co-infected patients, all baseline and follow-up HBV and HIV sequences were analysed, compared and correlated with treatment. Sequence alignments and phylogenetic studies for both HBV and vi HIV were conducted with MAFFT, Mega 4 and neighbour joining phylogenetic trees generated with the PHYLIP programme. Results: Three significant findings were observed in this study. Firstly, the majority of South African HIV patients enrolling for HAART were exposed to HBV infection and either had acute or chronic HBV infections. A total of 63.0% of patients were found to have one or more HBV markers, with 40.6% having detectable HBV DNA as an indication of replication. The study also detected 22.9% with positive HBsAg, and 23% of 77% HBsAg-negative patients having occult hepatitis B infection. Secondly, HBV/HIV co-infected patients do benefit during the management of HIV infections with lamivudine-containing HAART regimens. A total of 68.4% of patients responded to HAART, with undetectable HBV DNA during 18 to 24 months of follow-up. A total of 91.3% of HIV patients also responded to HAART with an undetectable HIV viral load during 6 to 12 months of follow-up. However, a total of 18% of patients had persistent HBV DNA, yielding various HBV virological responses against lamivudine containing-HAART regimens. This proportion of patients poses a question regarding the management of HBV and HIV coinfections, as guidelines on the use of HAART with anti-HBV activity from developed countries, may not necessarily be followed in developing countries. The results further showed that baseline drug-resistance was more frequent with HIV than HBV in this cohort of patients. The following HIV primary drug resistant mutants were observed: nine major NRT's primary mutants, M41L (1/30), E44A (1/30), V75M (1/30), F77L (1/30), V118I (1/30), M184V (1/30), L210S (1/30), T215Y (1/30) and V90I (1/30), and five major NNRT’s primary mutants were also detected, K103N (3/30), Y318CFSY (1/30), E138Q (1/30), P225H (1/30) and K238T. However, all followup samples had undetectable HIV viral load. In contrast to HIV, only one patient was detected with HBV mutant, M204I, at baseline. The mutant reversed to wild type during 6 months and other follow-up (12, 18 and 24 months). Finally, this study indicated that the HBV genotype A is still the most prevalent genotype circulating in South Africa. Of the 78 HBV sequences, 77 were genotype A and 1 sequence was genotype G. This is the first report from Africa of the detection of HBV genotype G. HIV subtype C remains the predominant prevailing subtype in South Africa. HBV genotype or HIV subtype C was not observed to influence any treatment outcome following treatment with vii lamivudine-containing HAART regimens. The study also indicated that patients on lamivudinecontaining HAART regimens do benefit not only by suppressing HIV and HBV viral load, but also improving immunity (i.e. CD4 cells count increases). Conclusion: Overall, the present study highlights the need for screening HBV before initiation of any HAART containing anti-HBV regimens in HBV/HIV co-infected patients. It necessitates the use of molecular assays for effective laboratory in diagnosis of occult HBV infections in HIVpositive patients, especially in developing countries where these assays are not widely available. While lamivudine-containing HAART regimens do benefit both HBV and HIV patients in co-infected individuals, however, whether HBV virological response is temporary or sustained is unknown at this stage. What is certain is that these patients require an effective monitoring programme as (1) a small percentage experience variable HBV virological responses (partial, reactivation, or no response), and (2) hepatitic flares are likely to develop if HAART is terminated (e.g. by patient), or the current HAART regimen is switched to another regimen without anti-HBV activity. HBV genotype A remains the dominant genotype in South Africa, but novel genotypes can be detected. HIV subtype C was found to be the prevalent subtype. HBV genotype or HIV subtype C were not seen to influence any treatment outcome following treatment with lamivudine-containing HAART regimens. Recommendations: HIV patients should be screened for HBV before initiation of anti-HBV containing HAART regimens. The screening of HBV in HIV patients is also important since some drugs included as part of HAART (e.g. nevirapine) may cause hepatotoxicity and exacerbate HBV infections leading to increased morbidity and mortality due to liver complications. Immunization and immune boosters of HIV patients with low (< 10IU/L) or no immunity against HBV should be done as this could be beneficial, although these patients may not respond optimally, or their immunity may wane faster due to immunocompromised status. Monitoring of both HBV and HIV resistant strains should be conducted for timely detection for the occurrence of multiple resistant mutations, which could limit future therapeutic option for both viruses.
Thesis (D Phil. (Medical Virology))--2008.
Keywords: antiretroviral therapy; HIV, Hepatitis B virus